THE ROLE OF AI IN EDUCATION: TRANSFORMING LEARNING THROUGH CHATGPT AND EMERGING TECHNOLOGIES - Murgai, Amol; Andure, Viddesh Bhaskar; Valiba, Darade Dnyaneshwar; Thorat, Rahul Gokul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Technology has always played a crucial role in education, but its use has expanded significantly with the increasing availability of smart devices and online learning materials. Artificial intelligence (AI) is used in various educational contexts to enhance student learning. AI enables round-the-clock access to teachers and lessons from any location. Through AI algorithms, it serves as a teaching tool, helping students achieve their goals by providing personalized feedback on assignments, quizzes, and other tasks. By automating routine tasks, AI can simplify life for everyone, saving time on repetitive chores like organizing emails or locating files. This paper examines the impact of emerging AI technologies in education.